2003
DOI: 10.1074/jbc.m302642200
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Fungal Lectin

Abstract: Aleuria aurantia lectin is a fungal protein composed of two identical 312-amino acid subunits that specifically recognizes fucosylated glycans. The crystal structure of the lectin complexed with fucose reveals that each monomer consists of a six-bladed ␤-propeller fold and of a small antiparallel two-stranded ␤-sheet that plays a role in dimerization. Five fucose residues were located in binding pockets between the adjacent propeller blades. Due to repeats in the amino acid sequence, there are strong similarit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
102
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(116 citation statements)
references
References 51 publications
14
102
0
Order By: Relevance
“…AAL has a six-fold ␤-propeller structure and forms six clefts between each blade, as determined from its crystal structure by Wimmerova et al (17) and Fujihashi et al (25). This fold is a type that is found in lectins of soil inhabitants and it displays multivalent carbohydrate recognition that has been proposed to be involved in the host recognition strategy of several pathogenic organisms, including the phytopathogenic bacterium R. solanacearum (17,26). AOL contains six sequence repeats that are highly similar to those of AAL, and it has been suggested that AOL also has a six-fold ␤-propeller structure (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AAL has a six-fold ␤-propeller structure and forms six clefts between each blade, as determined from its crystal structure by Wimmerova et al (17) and Fujihashi et al (25). This fold is a type that is found in lectins of soil inhabitants and it displays multivalent carbohydrate recognition that has been proposed to be involved in the host recognition strategy of several pathogenic organisms, including the phytopathogenic bacterium R. solanacearum (17,26). AOL contains six sequence repeats that are highly similar to those of AAL, and it has been suggested that AOL also has a six-fold ␤-propeller structure (17).…”
Section: Discussionmentioning
confidence: 99%
“…Another lectin that recognizes oligosaccharides containing core fucose would be a valuable tool in glycobiological research because only a few lectins have been identified as specific for core fucose, and AAL itself exhibits broad specificity for ␣1,2-, ␣1,3-, and ␣1,4-fucose-containing oligosaccharides (17). We previously identified a novel lectin, AOL, in iron-deficient cultures of the filamentous fungus A. oryzae; this lectin turned out to be L-fucose-specific from a hemagglutination inhibition assay using several monosaccharides and the encoding gene, fleA, was found to share 26% homology with AAL in primary structure (18).…”
mentioning
confidence: 99%
“…Homodimer 4 Gal na Entomotoxic (Hamshou et al 2013;Hamshou et al 2010b;Hamshou et al 2012;Skamnaki et al 2013) Bleuler-Martinez et al 2011;Fujihashi et al 2003;Fukumori et al 1990;Kochibe and Furukawa 1980;Olausson et al 2010;Olausson et al 2008;Tateno et al 2009;Wimmerova et al 2003) GlcNAc-β1,4-X na nd (Cioci et al 2006;Ueda et al 1999a;Ueda et al 2002;Ueda et al 1999b;Ueda et al 2003) Entomotoxic (Birck et al 2004;Bleuler-Martinez et al 2011;Damian et al 2005;Francis et al 2003;Jaber et al 2008;Jaber et al 2007;…”
Section: β-Trefoilmentioning
confidence: 99%
“…Members of the β-propeller-type family of mushroom lectins include hololectin AAL from the orange peel mushroom Aleuria aurantia (Fujihashi et al 2003;Wimmerova et al 2003) and its homologs from various ascomycetous molds such as AOL 1 from Aspergillus oryzae, and AFL from Aspergillus fumigatus (Houser et al 2015;Matsumura et al 2008) as well as PVL and LbTec2 from the basidiomycetes Psathyrella velutina and Laccaria bicolor (Cioci et al 2006;Wohlschlager et al 2014). Basidiomycetous PVL and LbTec2 show very low sequence homology to each other and to ascomycetous AAL (below 15 % sequence identity and 30 to 45 sequence similarity), while AFL and AOL 1 are highly homologous to each other (82 % sequence identity and 90 % similarity) and 30 % identical (60 % similar) to AAL.…”
Section: β-Propeller-type Lectinsmentioning
confidence: 99%
See 1 more Smart Citation